A Checklist of Scorpions in Iran (By 2017) - Kassiri, Hamid (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The present study aimed at compiling an updated checklist of scorpion species in 2017. Methods: scorpion, species, classification, Iran, and family were taken as keywords and were searched in the websites related to credible academic journals and scientific databases such as Web of Science, Ovid, PubMed, Systematic Review, SID, Iran Medex, Scirus, Google Scholar, and Medline. The search was more focused on species identification and included all articles published by 2017. A total of 150 articles were examined, of which 75 were selected as they involved the scorpion species found in Iran. Results and Discussion: Scorpions have attracted a great degree of attention, owing to possess a painful sting, poisonous venom, and sometimes fatal venom. In the past 50 years, scorpions have been studied from different biological and toxicological aspects in Iran. These efforts have been more focused on identifying different species of this animal. From among the 64 scorpion species reported in Iran, 86% belonged to the Buthidae family, 9.5% to the Hemiscorpiidae family, and 4.5% to the Scorpionidae family. The species were mainly reported to inhabit southern and southwestern Iran. The number of scorpion species reported in Iran has increased in the past 50 years. This trend will continue as more accurate studies are going to be conducted in this field. Conclusion: Iran is among the countries which have been reported to have a great number of species especial the dangerous ones.